2019
DOI: 10.3390/su11216033
|View full text |Cite
|
Sign up to set email alerts
|

Are Corporate Social Responsibility Courses Effective? A Longitudinal and Gender-Based Analysis in Undergraduate Students

Abstract: Despite the growing professional and academic interest in sustainability and corporate social responsibility (CSR) in recent decades, moral lapses continue to happen in the business arena. Because undergraduate students will be the managers and professionals of the future, training these students to be socially responsible is seen as critically relevant for reducing the likelihood of such moral lapses. However, the question of whether CSR courses can be effective is still debated and little is known about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 74 publications
0
15
1
Order By: Relevance
“…Reviewing the salient literature (Appendix A) suggests that extant knowledge regarding university students' attitudes towards SR is still in a developmental phase [14,19,22,23]. Indeed, a generalized lack of knowledge and training in SR among university students can be deduced [11][12][13]24,25]. There is also evidence to suggest that students and other groups perceive a need for learning about SR [26,27].…”
Section: Social Responsibility In University Classroomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviewing the salient literature (Appendix A) suggests that extant knowledge regarding university students' attitudes towards SR is still in a developmental phase [14,19,22,23]. Indeed, a generalized lack of knowledge and training in SR among university students can be deduced [11][12][13]24,25]. There is also evidence to suggest that students and other groups perceive a need for learning about SR [26,27].…”
Section: Social Responsibility In University Classroomsmentioning
confidence: 99%
“…Based on the conviction that university business students should be familiar with the SR concept and apply it to their future professional projects, we questioned their perceptions of this concept. To date, studies have shown a generalized lack of knowledge about SR [10][11][12], which is why Lämsä et al [13] demanded more empirical research on this subject. For Alonso-Almeida et al [14] little progress has been made since then (referring to the previous work), and research on attitudes to SR within the field of education is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If individuals become aware of their own deviations, they may put additional effort into shaping their future decision-making in a desired direction. In this context, improvement in reflective awareness would contribute to the better, more sustainable [54][55][56][57][58][59][60][61][62] ethical choices and reveal a possibility of an intervention design within the higher education framework. In addressing the question of how revealed regularities can be translated into nudges, we conclude that it is necessary to use additional questions and instruments in order to reveal underlying patterns and/or guidelines for decision-making in relation to those who selfidentify themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Reflective skills are recognized as important in education and its sustainability, and we propose the extension of that conclusion to business ethics. The relationship between the business ethics curriculum, sustainability and responsibility has previously been suggested as a prerequisite for shaping future decision-makers' attitudes and competences, as well as for building their integrity and morality [54][55][56][57][58]. Correspondingly, the reflective thinking proved to have an important role in development of quality learning and knowledge application to new and realistic situations [59,60], also, [61] show that reflective (and cooperative) learning environment enable development of competences for sustainability.…”
Section: Novel Theories In Business Ethicsmentioning
confidence: 92%